DiMIZA: A dispersion modeling based impact zone assessment of mercury (Hg) emissions from coal‐fired power plants and risk evaluation for inhalation exposure. Issue 7 (29th December 2020) - Karaca, Ferhat; Kumisbek, Aiganym; Inglezakis, Vassilis J.; Azat, Seitkhan; Zhakiyenova, Almagul; Ormanova, Gulden; Guney, Mert
Abstract: Coal‐fired combined heat and power plants (CHPPs) serving large districts are among the major sources of mercury (Hg) emissions globally, including Central Asia. Most CHPPs reside on the outskirts of urban areas, thus creating risk zones. The impact of atmospheric Hg levels on health is complex to establish due to the site‐specific nature of the relationship between CHPP emissions and hotspots (i.e., localized areas where Hg concentrations greatly exceed its background value). However, a methodological identification of "emission impact zones" for atmospheric Hg emissions from CHPPs with potential adverse public health outcomes has not yet been fully studied. The present work suggests an easy‐to‐use and cost‐free impact zone identification method based on HYSPLIT dispersion modeling for atmospheric Hg emissions from CHPPs. The dispersion modeling based impact zone assessment, DiMIZA, merges short‐term dispersion runs (e.g., hourly) into long‐term emission impacts (e.g., yearly), which allows to identify the source impact zones. To perform a case study using the suggested method, a CHPP plant in Nur‐Sultan (capital of Kazakhstan) was selected. First, traditional ad‐hoc measurements were performed to identify the level of dispersions at ground level in different atmospheric stability characteristics. Then, HYSPLIT dispersion model was run for the same days and times of those particular periods when the field measurements were performed. The model results were evaluated via a comparison with the ground measurements and assessed for their atmospheric stability and diel conditions. Due to different emission loads in heating and non‐heating periods, two separate pairs of impact zone maps were generated, and public Hg exposure health risks (acute and chronic) were assessed. Abstract : The present study offers a new method, DiMIZA, a dispersion modeling based impact zone assessment, for the identification of the emission impact zones and health risk zones for mercury (Hg) exposure risk assessment studies for coal‐fired combined heat and power plant (CHPP) emissions based on HYSPLIT dispersion modeling. A case assessment was also performed for Nur‐Sultan City (Kazakhstan) to evaluate the method. The results here presented indicate the potential of HYSPLIT based dispersion modeling as a tool for an improved understanding of the impacts of power plants and their impact and risk zones.